"Chasing a passion": first-generation college graduates at work. Issue 4 (11th April 2016) - Olson, Joann S.
Abstract : Purpose: – The purpose of this paper is to describe the college-to-work transition as experienced by first-generation college (FGC) graduates. First-generation graduates are often adjusting to workplaces that are significantly different from parents' work environments. Design/methodology/approach: – This phenomenological study explored the early-career learning experiences of six FGC graduates from the USA. All participants were working full-time and had graduated two to six years earlier. Findings: – Three themes were identified: starting the job, being in the job, and releasing the past. Participants highlighted unanticipated aspects of their college-to-work transition, including dealing with workplace politics and family dynamics. They also described ambivalence between their current work and the desire to pursue a more compelling career or vocational passion. Research limitations/implications: – All participants were white and from similar (rural) settings in one region of the USA. The qualitative nature of the study restricts generalization. Practical implications: – This study suggests, given the distinction between first-generation students' post-college work environments and that of their parents, that educators' efforts to assist FGC students might appropriately extend to topics beyond graduation. FGC graduates should be alerted to the impact of shifts in social and cultural norms, and informed about changing family dynamics that may continue after leaving school. Originality/value: – Previous research has highlighted the challenges facing FGC students. This is one of few studies that explores the experiences of FGC graduates in the workplace following graduation.